2016
DOI: 10.5902/1980509822743
|View full text |Cite
|
Sign up to set email alerts
|

Fungos Micorrízicos Arbusculares: Composição, Comprimento De Micélio Extrarradicular E Glomalina Em Áreas De Mata Atlântica, Rio De Janeiro

Abstract: A Mata Atlântica é considerada um ambiente de ampla biodiversidade, no entanto, por estar constantemente sendo submetida a uma intensa pressão antrópica, encontra-se bastante fragmentada e desconectada, circundada por extensas matrizes formadas de pastos, capoeiras, monoculturas e áreas urbanas. A fragmentação, bem como determinados sistemas de uso e manejo do solo, pode ocasionar alterações na composição e atividade de microrganismos do solo, como os fungos micorrízicos arbusculares (FMAs). Dessa forma, o tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 1 publication
0
6
0
3
Order By: Relevance
“…Higher T-GRSP levels in the forest area than those in the TA may be associated with the temporal accumulation of this protein. Silva et al (2016) showed that GRSP levels are higher in secondary forest areas than in crop areas. It is not yet clear which factors control the production of GRSP in the environment.…”
Section: Glomalin-related Soil Proteinmentioning
confidence: 99%
“…Higher T-GRSP levels in the forest area than those in the TA may be associated with the temporal accumulation of this protein. Silva et al (2016) showed that GRSP levels are higher in secondary forest areas than in crop areas. It is not yet clear which factors control the production of GRSP in the environment.…”
Section: Glomalin-related Soil Proteinmentioning
confidence: 99%
“…This result was associated with low soil moisture content and high soil temperature (Table 1) and might have been influenced by the higher density of thin roots in this ecosystem. The stressful microclimatic conditions often observed in pastureland, as opposed to Atlantic Forest sites at different stages of succession, favor the production of AMF survival structures (Silva et al, 2016). Factors such as low anthropogenic interference, high microclimate stability, and soil fertility explain the lower number of spores in the analog agroforestry site (Table 3).…”
Section: /7mentioning
confidence: 99%
“…Sendo assim, além dos fungos micorrizos arbusculares possibilitarem uma maior absorção de nutrientes, são capazes de promoverem uma maior resistência da planta a condições de estresse hídrico, Development, v. 9, n. 9, e947998066, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.8066 exercendo influência tanto na agregação do solo como no controle de patógenos. A agregação do solo ocorre por meio de diferentes mecanismos, como a produção de glicoproteína ou glomalina, que favorece tanto na estabilidade dos agregados, como diversos são os estudos que a apontam como uma relevante armazenadora de carbono e nitrogênio no solo (Silva, Pereira, Santos, Miguel & Silva 2016).…”
Section: Fungos Micorrizos Arbusculares -Fmasunclassified